Adolescents: Typically developing siblings and siblings with severe disability - Harty, M; Alant, E; Opperman, S (Social Work/Maatskaplike Werk, 2002)
The aim of this study was to establish adolescents' perceptions of their siblings with a severe disability as well as the degree and type of social support they utilise. Seventeen adolescents with siblings with a severe disability were interviewed using a semi-structured interview. A control group of adolescents with normal functioning siblings also took part in the research project as it is essential to distinguish between perceptions and attitudes that are characteristic of sibling relations in general and those which are a direct result of the presence of a sibling with a severe disability. Interviews were conducted with 25 adolescents between the ages of 12-16. The data were analysed in a qualitative manner according to 9 categories. Results showed that guilt feelings were more frequently experienced amongst the adolescents with siblings with a severe disability and these subjects tended not to freely express their feelings about their sibling with a disability. Amongst the control group the majority of the adolescents had a positive cognitive appraisal of their normal functioning siblings, although these adolescents did express ambivalent emotions towards the sibling relationship.